Brand image, cultural events and loyalty in mobile industry - Thelma Valéria Rocha; Natália Hara Katayama; Christophe Fabien Fuhrer; Thereza Cherubini (Revista Produção Online, 2013)
: This study analyses the effect of cultural events in brand image and customers’ loyalty in the mobile industry. The main relevance is to discuss the effectiveness’ of cultural events, those demanding high investments’ for the companies which have to explain the results in terms of loyalty and brand image. The subject is reviewed theoretical considering three topics: cultural events, brand image and loyalty, which lead to hypotheses to be tested. The field research of a quantitative nature uses the survey method, which was applied to 150 teenagers consumers of mobiles companies, classes A and B. The results of field research show that there is a positive relationship between cultural activities and brand image, and between the brand image and loyalty. However, there was significant correlation between cultural events and loyalty only to B Company. It may be related with B events wish were prepared to this target and may improve loyalty. To companies as A and C, brand image acts as moderator between cultural events and loyalty. These results indicated that cultural events may have impact in loyalty, since the company developed those actions to the target. As contribution, this study fills a gap which is the study that discusses effect of cultural activities on brand image and loyalty, in emerging economies, as Brazil, where few researches consider cultural events.